TO THE ISSUE OF INNOVATIVE DEVELOPMENT OF RAILWAY TRANSPORT IN KAZAKHSTAN - N. L. Makhatova; A. M. Bakirbekova; V. Sharff (Scientific Journal of Pedagogy and Economics, 2019)
The article discusses the issues of innovative development of railway transport, based on the targets of the “State program of infrastructure development “Nurly Zhol” for 2015 - 2019” and “Development strategy of JSC "NC "KTZ" until 2025”. Innovative development of railway transport is determined through the current state of the company, which provide their innovative services in the industry. At the same time, it is known that in Kazakhstan its operator provides access to the main railway network, which is a natural monopolist of this industry in the person of National Company Kazakhstan Temirjoly JSC "NC "KTZ". Railway transport is functionally divided into two parts: the main activity is the transportation of passengers and baggage transportation, which is carried out through several leading specialized companies belonging to JSC "NC "KTZ" as: Passenger transportation JSC, Zholaushylartrans Company, JSC Suburban Transportation, JSC Passenger Leasing Carriage Company, JSC Passenger Leasing Carriage Company. Based on the activities of the companies noted, there was considered the innovative orientation of the strategy and tactics of railway transport development within the framework of a mixed natural-monopoly and market mechanism. The factors constraining innovation development are also described, and the conditions for improving innovation activity in railway transport are proposed.